Multidrug chemotherapy causes early radiological signs of loosening in distal femoral replacements. Issue 7 (July 2020) - Mumith, Aadil; Coathup, Melanie; Edwards, Thomas C; Gikas, Panos; Aston, Will; Blunn, Gordon
Abstract : Aims: Limb salvage in bone tumour patients replaces the bone with massive segmental prostheses where achieving bone integration at the shoulder of the implant through extracortical bone growth has been shown to prevent loosening. This study investigates the effect of multidrug chemotherapy on extracortical bone growth and early radiological signs of aseptic loosening in patients with massive distal femoral prostheses. Methods: A retrospective radiological analysis was performed on adult patients with distal femoral arthroplasties. In all, 16 patients were included in the chemotherapy group with 18 patients in the non-chemotherapy control group. Annual radiographs were analyzed for three years postoperatively. Dimensions of the bony pedicle, osseointegration of the hydroxyapatite (HA) collar surface, bone resorption at the implant shoulder, and radiolucent line (RLL) formation around the cemented component were analyzed. Results: A greater RLL score (p = 0.041) was observed at three years postoperatively, with those receiving chemotherapy showing greater radiological loosening compared with those not receiving chemotherapy. Chemotherapy patients experience osteolysis at the shoulder of the ingrowth collar over time (p < 0.001) compared with non-chemotherapy patients where osteolysis was not observed. A greater median percentage integration of the collar surface was observed in the non-chemotherapy group (8.6%, interquartile range (IQR) 0.0% to 37.9%; p = 0.021) at three years. Bone growth around the collar was observed in both groups, and no statistical difference in amount of extracortical bony bridging was seen. Conclusion: Multidrug chemotherapy affects the osseointegration of ingrowth collars and accelerates signs of radiological loosening. This may increase the risk of aseptic loosening in patients with massive segmental implants used to treat bone cancer. Cite this article: Bone Joint Res 2020;9(7):333–340.